Identification of Phenolic Compounds and Assessment of the Antioxidant and Antibacterial Properties of Thymelaea microphylla Coss. et Dur. from Western Algerian Sahara (Ain-Sefra Province) - Allam, Hanane; Bennaceur, Malika; Ksouri, Riadh; Sahki, Rabéa; Marouf, Abderrazak; Benamar, Houari (Jordan Journal of Pharmaceutical Sciences, 2020)
Thymelaea microphylla is a medicinal plant commonly used in the Algerian Sahara traditional medicine and has a chemical composition with therapeutic properties. In the current study, the antioxidant activities of the ethyl acetate, methanol, and aqueous extracts from aerial parts of T. microphylla were evaluated by means of phosphomolybdenum, 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), β-carotene bleaching, and reducing power assays. Antibacterial effect was also determined using disc diffusion method. The tested samples exhibited an important antioxidant effects by scavenging free radicals, inhibition of β-carotene oxidation, and by acting as reducing agents. The high antioxidant capacity was found in extracts with high phenolic content. Methanol extract with high content of phenolic compounds and flavonoids showed the best antioxidant effect. The extracts showed also antibacterial activity against human pathogenic bacteria. Methanol extract was the most active among the tested extracts against Gram-positive and Gram-negative bacteria. The high-pressure liquid chromatography (HPLC)-UV-diode array detector (DAD) analysis leads to the identification of phenolic acids, flavonoid glycosides and aglycones. The results suggest a possible application of T. microphylla as a potential natural source of bioactive compounds with antioxidant and antibacterial activities.